Urine Output as a Novel Predictor for In-Hospital Mortality in Acute Pulmonary Embolism Patients: Training With the MIMIC Database and Validation With Independent Cohort - Wenjia Ai; Fangfei Li; Qilin Yang; Jingluo Qiu; Aiqiang Zhou; Yinqian Huang; Baohui Xu; Zhihui Zhang (Cardiovascular Therapeutics)
Conclusion: Our study revealed a negative association of urine output with in-hospital mortality in acute pulmonary embolism patients, with the optimal urine output being significantly higher than the value of other critical illnesses.